(untitled) (Analele Universității București. Limba și literatură română, 2024)
Since 2010, ideology has become more present in Romanian contemporary literature, denouncing the literary canon and its function in nowadays society. Female authors started to be more committed to a feminist agenda, which resulted into a process of (re)claiming female identities and experiences and also creating new forms of defining what being a woman means. After the 1989 Romanian Revolution, artists finally use their right to freedom of speech, being more involved into the social and political aspects of art and society. In this paper, I shall focus on Medeea Iancu’s poetry, analysing her discourse and how she develops a feminist agenda in Romania. I shall also point out the fact that her discourse evolves from Divina tragedie [The Divine Tragedy] (2011) and Cîntarea care a biruit toate cîntările [The Song that Overcame All Songs] (2015) to what is known as a feminist manifesto in Delacroix este tabu: Suita romînească [Delacroix is Taboo: The Romanian Suite] (2017) and Delacroix este tabu: Amendamentele lirice [Delacroix is Taboo: The Lyrical Amendments] (2019). Nevertheless, in this research I shall showcase the aspects that are representative for the feminist literary movement in Romania, focusing mainly on Medeea Iancu, as she embodies the image of the feminist poet.